Model for the prediction of mechanical asphyxia as the cause of death based on four biological indexes in human cardiac tissue. Issue 3 (May 2021) - Han, Liujun; Li, Wencan; Hu, Yikai; Zhang, Heng; Ma, Jianlong; Ma, Kaijun; Xiao, Bi; Fei, Geng; Zeng, Yan; Tian, Lu; Chen, Long
Highlights: According to the AUC, DUSP1, KCNJ2, miR-122, and miR-3185 all had high accuracy in identifying mechanical asphyxia death. The first molecular prediction model using multiple indexes for determining death by mechanical asphyxia was established. No false positive and false negative were detected by using this prediction model in the single blind experiment. Abstract: Determination of mechanical asphyxia as the cause of death has always been difficult for forensic pathologists, particularly when signs of asphyxia are not obvious on the body. Currently, depending on only physical examination of corpses, pathologists must be cautious when making cause-of-death appraisals. In a previous study, four biomarkers—dual-specificity phosphatase 1 ( DUSP1 ), potassium voltage-gated channel subfamily J member 2 ( KCNJ2 ), miR-122, and miR-3185—were screened in human cardiac tissue from cadavers that died from mechanical asphyxia compared with those that died from craniocerebral injury, hemorrhagic shock, or other causes. Expression of the markers correlated with death from mechanical asphyxia regardless of age, environmental temperature, and postmortem interval. However, a single biological index is not an accurate basis for the identification of the cause of death. In this study, receiver operating characteristic curves of the ΔCq values of the four indexes were generated. The diagnostic accuracy of the indexes was judged according to their area under the curve ( DUSP1 : 0.773, KCNJ2 : 0.775, miR-122: 0.667, and miR-3185: 0.801). Finally, a nomogram was generated, and single blind experiment was conducted to verify the cause of death of mechanical asphyxia.